Analisis Pengaturan Layout Gudang Sparepart Menggunakan Metode Dedicated Storage pada Bengkel Saerah Baru Motor di Sragen - Friska Oktaviani; Erni Widajanti; Sunarso Sunarso (Jurnal Manajemen Riset Inovasi, 2024)
The MSME Saerah Baru Motor workshop in Sragen is an MSME that operates in the field of selling goods and motorbike repair services in Masaran, Sragen. Saerah Baru Motor Workshop tries to organize spare parts warehouse layout planning with the right layout system. The problem in this research is whether the application of the Dedicated Storage method can streamline the layout of the spare parts warehouse at the Saerah Baru Motor workshop in Sragen. The use of this research is as a consideration for MSMEs at the Saerah Baru Motor workshop to streamline the layout of spare parts warehouses and can be used to make decisions regarding efficiency.This research uses the Dedicated Storage method at the Saerah Baru Motor workshop in Sragen. The data required is a general description of the Saerah Baru Motor workshop in Sragen, item size data, storage capacity data and average transfer data for incoming and outgoing goods. Data sources include primary data and secondary data. Data collection techniques using observation, interviews and documentation. Data analysis techniques use quantitative. The results of this research indicate that the layout of the spare parts warehouse at the Sarah Baru Motor workshop is not efficient. This is proven by the absence of separation of types of spare parts, meanwhile, the results of calculations using the Dedicated Storage method are that there is a separation of wet spare parts from solid spare parts and the placement of items is adjusted and sorted based on the assignment value of each item, namely the item that has a high assignment value is the spark plug with a value of 17.47826 will be placed close to the place where consumers come to buy spare parts.